2016
DOI: 10.1177/0706743716639054
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Attempted Suicide from the Emergency Room of 2 General Hospitals in Montreal, Canada

Abstract: Introduction: The epidemiology of attempted suicide has not been well characterized because of lack of national data or an International Classification of Diseases (ICD) code for suicide attempts. We conducted a retrospective chart review in 2 adult general hospitals (tertiary and community) in Montreal, Canada, in 2009-2010 to 1) describe the characteristics of men and women who presented to the emergency department (ED) and/or were hospitalized following a suicide attempt, 2) identify factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Individuals that attempted suicide identified by only nurses triage notes were included. Similar findings showed that more than half of attempted suicide presentations remained "silent" (went undetected) if nurses' notes were ignored (Daneau, 2016;Rahme et al, 2016). Another strength is that our study can be reproduced in all Quebec's hospital and probably any Canadian hospital since the medical records systems respond to provincial and even Canadian accreditation standards.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Individuals that attempted suicide identified by only nurses triage notes were included. Similar findings showed that more than half of attempted suicide presentations remained "silent" (went undetected) if nurses' notes were ignored (Daneau, 2016;Rahme et al, 2016). Another strength is that our study can be reproduced in all Quebec's hospital and probably any Canadian hospital since the medical records systems respond to provincial and even Canadian accreditation standards.…”
Section: Discussionsupporting
confidence: 54%
“…These 369 individuals were identified from a total of 5746 reviewed charts. The details of this process is thoroughly described in Rahme et al (2016).…”
Section: Systematic Search Data Extraction and Coding Manual Developmentioning
confidence: 99%
“…As our sensitivity analyses showed similar risk patterns of suicide attempt and suicidal death by mental disorders, and the risk patterns of suicide attempt and suicidal death across males and females as existed in the literature, such combination was justifiable. While we used ICD-9 and ICD-10 case definitions for suicide diagnostic data contained in the administrative databases (DAD and mortality database), as recommended by Statistics Canada, the diagnostic data are likely to underestimate the prevalence of suicide, specifically attempts ( Rahme et al, 2016 ), since not all attempts require hospitalization. This could have diluted the observed association biased towards the null.…”
Section: Discussionmentioning
confidence: 99%
“…Since health care is primarily a provincial/territorial responsibility, much of the data from EDs is housed in clinical information systems such as electronic health records (EHRs). Studies from several provinces have shown that extracting ED data on suicidal behaviour from clinical databases is feasible [ 64 66 ]. However, provincial/territorial EHR systems are varied, and some do not use standardized codes for diagnoses, making it difficult to accurately and consistently capture cases of self-injury.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of emergency department visits used “suicide-related behaviour” and “self-harm” with inclusive definitions that captured non-fatal suicide attempts due to self-poisoning or self-injury, along with events with undetermined intent [ 65 , 86 ]. Inclusive definitions are used by national statistical agencies because ICD codes under-estimate suicide attempts by more than 50% [ 61 , 66 , 87 ].…”
Section: Introductionmentioning
confidence: 99%